ChemInform Abstract: Synthesis of New Furopyrans (III) and Angularly Fused Furopyranochromenes (V) from 3‐Arylmethylidenefuran‐2‐ones. Issue 16 (22nd April 2014) - Anis'kova, T. V.; Egorova, A. Yu.
Abstract The title compounds (III), (V) are obtained in reactions of appropriate 5‐aryl‐3‐arylmethylidenefuran‐2‐ones (I) or (IV) with malononitrile.